Locomotor problems among rural elderly population in a District of Aligarh, North India - Maroof, Mohd (J Family Med Prim Care, 2017)
INTRODUCTION: Locomotor functions decline with the age along with other physiological changes. This results in deterioration of the quality of life with decreased social and economic role in the society, as well as increased dependency, for the health care and other basic services. The demographic transition resulting in increased proportion of elderly may pose a burden to the health system. OBJECTIVES: To find the prevalence of locomotor problems among the elderly population, and related sociodemographic factors. MATERIALS AND METHODS: The study was a community-based cross-sectional study done at field practice area of Rural Health Training Centre, JN Medical College, AMU, Aligarh, Uttar Pradesh, India. A sample of 225 was drawn from 1018 elderly population aged 60 years and above using systematic random sampling with probability proportionate to size. Sociodemographic characteristics were obtained using pretested and predesigned questionnaire. Locomotor problems were assessed using the criteria used by National Sample Survey Organization. Data were analyzed using SPSS version 20. Chi-square test was used to test relationship of locomotor problems with sociodemographic factors. P <0.05 was considered statistically significant. RESULTS: The prevalence of locomotor problems among the elderly population was 25.8%. Locomotor problems were significantly associated with age, gender, and working status whereas no significant association with literacy status and marital status was observed. CONCLUSION: The study concluded that approximately one-fourth of the elderly population suffered from locomotor problems. The sociodemographic factors related to locomotor problems needs to be addressed properly to help them lead an independent and economically productive life.